Evaluation of Computer and Network Engineering Field Work Practice Program Based on Context Input Process Product Model: Evaluasi Program Praktik Kerja Lapangan Teknik Komputer dan Jaringan Berbasis Model Context Input Process Product - Kristanto, Eko; Yayuk, Erna; Soenaryo, Siti Fatimah (Universitas Muhammadiyah Sidoarjo, 2025)
Vocational education plays a crucial role in preparing students to meet the demands of the industrial world. At SMK Muhammadiyah Ngawen, the implementation of the Field Work Practice (PKL) program is evaluated using the CIPP (Context, Input, Process, Product) model to assess its effectiveness comprehensively. Despite the importance of PKL, few studies have thoroughly evaluated its alignment with industrial needs using a structured evaluation model. This study aims to analyze the implementation of PKL evaluation at SMK Muhammadiyah Ngawen through qualitative methods, including observation, semi-structured interviews, and documentation. The results indicate that the PKL evaluation is conducted effectively, supported by solid collaboration between schools and industrial partners, and has enhanced students' practical skills and job readiness. The novelty of this study lies in its structured use of the CIPP model in a vocational setting to identify gaps between school training and industry expectations. The implications suggest the need for broader industry partnerships and curriculum adjustments to strengthen the relevance of PKL programs in vocational education. Highlights: Highlights effective PKL evaluation using the CIPP model. Reveals strong school-industry collaboration in vocational training. Recommends curriculum alignment with industry needs. Keywords: Field Work Practice, CIPP Model, Vocational Education, Skill Development, Industry Partnership